Застосування квітів гібіскусу у виробництві натуральних барвників - Шпачук, М. А.; Точона, Анастасія Сергіївна; Рубанка, Катерина Володимирівна; Терлецька, Віта Альбертівна (My University, 2017)
В роботі представлено можливість застосування квітів гібіскусу, як сировини для створення натурального червоного барвника. Визначено хімічний склад квітів гібіскусу та доведена її висока харчова цінність. The paper presents the possibility of applying hibiscus flowers as raw materials for the production of a natural red dye. The chemical composition of flowers of hibiscus has been determined and its high nutritional value has been proved The paper presents the possibility of applying hibiscus flowers as raw materials for the production of a natural red dye. The chemical composition of flowers of hibiscus has been determined and its high nutritional value has been proved.
Keywords: квіти гібіскусу; екстракт; барвник; хімічний склад; цветы гибискуса; экстракт; краситель; химический состав; flowers of hibiscus; extract; dye; chemical composition; кафедра технології консервування